Analisa Pengaruh Belokan Tajam pada Pipa Besi Terhadap Perpindahan Panas pada Solar Water Heater - Thaib Razali; Ahmad Syuhada; Ulul Rizza Jumada (Jurnal Teknik Mesin Unsyiah, 2019)
Solar energy is a renewable energy. In Indonesia the potential for renewable energy is very abundant but there is no optimal utilization. The use of solar energy, one of which is to use solar collectors to collect solar thermal energy. Solar water heater is a device that uses solar radiation and converts it into thermal energy. To get the most out of the collector, many ways can be done, one of which is the influence of the distance between the pipe passages, the length of the pipe passage and the diameter of the pipe bends. Then the closer the distance between the passage of the pipe will get the results of greater collector efficiency. In this research, the effect of sharp turns on the pipe with a total length of 4 meters is varied into 4 pipe length variations (70, 30, 20) cm and the shape of the Circle on the heat transfer of the solar water heater. From the research with the sun intensity of 691 W / m2 occurred in collector C (20 cm). The optimal results obtained are an outlet temperature of 64 OC with useful heat energy of 447.69 W / m2 and an efficiency of 89.98%, occurring at 14.00 WIB.